PERANCANGAN KOLEKSI PA’SURRA TORAYA SEBAGAI SELFSTATEMENT GAYA HIDUP WANITA URBAN - FEI SIEN JESICA; DEWI ISMA ARYANI; PETER MULJONO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2017)
Indonesia's cultural diversification, including the Toraja carving, has inspired the design of ready-to-wear deluxe fashion collection entitled